2018
DOI: 10.1155/2018/9012352
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Pterostilbene and Resveratrol on Biomechanic, Biochemical, and Histological Parameters in Streptozotocin‐Induced Diabetic Rats

Abstract: Aims The aim of this study was to investigate the effects of pterostilbene (PTS) (trans-3,5-dimethoxy-4′-hydroxystilbene) and resveratrol (RSV) (trans-3,5,4′ trihydroxystilbene) applied at different doses for the treatment of streptozotocin- (STZ-) induced diabetic rats. Materials and Methods At the end of the 5-week experimental period, the right gastrocnemius muscles of the rats were examined biomechanically, while the left ones were examined histologically. In addition, blood glucose, serum insulin, and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Since oxidative stress is a pivotal factor in the DM pathogenesis and complications, studies have emerged aiming to increase the antioxidant response and reducing the oxidative impacts by the investigation Nrf2 activators [34,44,45,46]. In vitro studies, animal models, and clinical trials suggest that the up-regulation of the Nrf2 pathway can be protective against DM (T1 and T2) by suppressing the disease progression and preventing complications [32,47,48,49]. This evidence encourages the activation of Nrf2 as a target against diabetes; however, more studies are necessary to evaluate this effect.…”
Section: Type-2 Diabetesmentioning
confidence: 99%
“…Since oxidative stress is a pivotal factor in the DM pathogenesis and complications, studies have emerged aiming to increase the antioxidant response and reducing the oxidative impacts by the investigation Nrf2 activators [34,44,45,46]. In vitro studies, animal models, and clinical trials suggest that the up-regulation of the Nrf2 pathway can be protective against DM (T1 and T2) by suppressing the disease progression and preventing complications [32,47,48,49]. This evidence encourages the activation of Nrf2 as a target against diabetes; however, more studies are necessary to evaluate this effect.…”
Section: Type-2 Diabetesmentioning
confidence: 99%
“…Streptozotocin (STZ) and alloxan, used to induce type 1 diabetes mellitus in rats, mice or rabbits, are glucose analogues that penetrate pancreatic β cells and induce their demise [40]. Unlike other authors who have used STZ to induce diabetes in rats [41][42][43][44], we observed no significant difference in weight ( Figure 2A) and blood glucose levels ( Figure 2B) between diabetic and Pter-treated diabetic rabbits. This can be understood by the fact that the cytotoxic effect of STZ and alloxan is achieved by different molecular pathways [40], or by an insufficient Pter concentration, which was able to reverse hyperglycaemia with alloxan induction in our experimental model.…”
Section: Discussionmentioning
confidence: 60%
“…So far, the proautophagic activity of Pt was mostly investigated in cancer cell lines and tumorigenic conditions ( Lee et al, 2019 ; Ma et al, 2019 ), whereas much less is known about it in other physiological and pathological conditions. For skeletal muscle, the studied effects of Pt administration have mainly regarded insulin sensitivity ( Gómez-Zorita et al, 2015 ; Tastekin et al, 2018 ) and muscle adaptation to exercise ( Zheng et al, 2020 ), but autophagy was not investigated in those studies. In light of this, we investigated the autophagy-modulating action of Pt in fibroblast cultures and in skeletal muscle of wild-type and COL6 null mice, and found that Pt treatment potently induces the autophagic flux and is able to ameliorate the muscle pathology of COL6 null animals.…”
Section: Introductionmentioning
confidence: 99%